2017
DOI: 10.14814/phy2.13089
|View full text |Cite
|
Sign up to set email alerts
|

Impaired myogenic response of the afferent arteriole contributes to the increased susceptibility to renal disease in Milan normotensive rats

Abstract: Milan normotensive (MNS) rats are more susceptible to the development of renal disease than Milan hypertensive (MHS) rats, but the genes and pathways involved are unknown. This study compared the myogenic response of isolated perfused afferent arterioles (Af‐Art) and autoregulation of renal blood flow (RBF) and glomerular capillary pressure (Pgc) in 6–9‐week‐old MNS and MHS rats. The diameter of the Af‐Art of MHS rats decreased significantly from 14.3 ± 0.5 to 11.5 ± 0.6 μm when perfusion pressure was elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The Milan normotensive strain has also recently proved useful for investigating genetic mechanisms mediating impaired myogenic responses and susceptibility to development of proteinuria and renal injury. 56…”
Section: Platforms Of Experimental Hypertension: Geneticmentioning
confidence: 99%
See 1 more Smart Citation
“…The Milan normotensive strain has also recently proved useful for investigating genetic mechanisms mediating impaired myogenic responses and susceptibility to development of proteinuria and renal injury. 56…”
Section: Platforms Of Experimental Hypertension: Geneticmentioning
confidence: 99%
“…The various genetic rat strains can be used as models of slowly developing primary hypertension, 48,67,68 juvenile hypertension, 69,70 salt-induced hypertension, 51 and hypertension associated with end-organ damage. 56 However, understanding the genetic composition of the hypertensive strain and choosing an appropriate control strain are important. 66 A direct comparison of 2 strains of commonly used DSS rats demonstrated >1.3 million different base pairs (bps) between the strains and a significant difference in BP when the rats were fed a high-salt diet.…”
Section: Platforms Of Experimental Hypertension: Geneticmentioning
confidence: 99%
“…The auto-regulatory feedback mechanisms that maintain renal blood flow (RBF) and glomerular filtration rate (GFR) over a wide range of haemodynamic pathophysiological conditions can be disturbed in metabolic and inflammatory disease states promoting the progression of nephropathy [1][2][3]. Measuring and interpreting altered renal perfusion at baseline and in response to physiological stressors would facilitate assessment of individuals at risk of kidney disease or its complications, and assist in the development of pharmacological interventions [4].…”
Section: Introductionmentioning
confidence: 99%
“…RBF raised about 40%, whereas stop‐flow pressure only elevated by about 20% when renal perfusion pressure increased from 100 to 140 mmHg (Ge et al. ).…”
mentioning
confidence: 99%
“…A recent study by Ge et al. () provided a potential mechanism for the difference in diabetes‐associated kidney injury between MNS and MHS rats. They demonstrated that normotensive rats with impaired autoregulation developed severe diabetic kidney injury, in contrast, the hypertensive rats with intact autoregulation were protected from diabetic kidney injury.…”
mentioning
confidence: 99%